2015
DOI: 10.1111/jopr.12433
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Fractured Multiunit Maxillary Implant‐Supported Fixed Prosthesis with Stripped Abutment Screws Using a Hybrid Cement‐Retained and Screw‐Retained Design: A 5‐Year Follow‐Up Clinical Report

Abstract: Fracture and loosening of implant-supported prostheses (ISPs) are complications encountered in routine dental practice. In the present report, management of a fractured maxillary full-arch cement-retained (CR) fixed dental prosthesis supported by six implants is presented. Due to stripped screws, complications were encountered that prevented the retrieval of two of the six abutment screws, which was managed by using a hybrid retention approach, whereby a single full-arch CR and screw-retained (SR) ISP was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Studies suggests the method used for implant prosthesis retention (cement or screw‐retained restorations) is associated with the initiation and progression of peri‐implant soft tissue inflammation and CBL. Stagnation of residual cement in the peri‐implant tissues after prosthesis fixation can incite soft tissue inflammation and CBL . In this regard, excess cement at the time of prosthesis loading needs to be removed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggests the method used for implant prosthesis retention (cement or screw‐retained restorations) is associated with the initiation and progression of peri‐implant soft tissue inflammation and CBL. Stagnation of residual cement in the peri‐implant tissues after prosthesis fixation can incite soft tissue inflammation and CBL . In this regard, excess cement at the time of prosthesis loading needs to be removed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 26,27 suggests the method used for implant prosthesis retention (cement or screw-retained restorations) is associated with the initiation and progression of peri-implant soft tissue inflammation and CBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that the method used for fixation of prosthesis (screw‐retained [SR] or cement‐retained [CR]) following implant placement influences implant survival. Although screw‐ and CR implant restorations have been used in implant‐retained restorations, neither methodology is shown to be advantageous over the other .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all implants were restored with screw‐retained restorations. Studies have suggested that the method used for the retention of the implant prostheses is an essential parameter that influences the overall success and survival of dental implants. Although cements are commonly used for the restoration of dental implants; presence of residual cement within the peri‐implant sulci results is a risk‐factor for peri‐implant mucositis and peri‐implantitis .…”
Section: Discussionmentioning
confidence: 99%